2008
DOI: 10.1055/s-2008-1038768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Heat Stress (35 °C) with Simulated Air Movement on the Thermoregulatory Responses during a 4‐km Cycling Time Trial

Abstract: The aim of the present investigation was to examine the influence of environmental heat stress (35 degrees C) on 4-km cycling time trial performance using simulated environmental conditions and facing air velocities that closely reflect competitive situations. Nine competitive cyclists (age 34 +/- 5 years, maximal oxygen uptake 61.7 +/- 8.6 ml . kg (-1) . min (-1)) completed a simulated 4-km cycling time trial in laboratory ambient temperatures (dry bulb temperatures) of 35 degrees C and 13 degrees C (relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 37 publications
2
35
2
2
Order By: Relevance
“…Heat-stress (Figure 5) had a significant, negative impact on time-trial performance from a sample of 14 MPO data points per trial section MPO and for the whole trial MPO across 11 included studies (MD = −24.79 W, 95% CI = −39.52 to −10.06, p = 0.001) (Tatterson et al, 2000; Tucker et al, 2004; Abbiss et al, 2008; Altareki et al, 2009; Peiffer and Abbiss, 2011; Périard et al, 2011; Castle et al, 2012; Périard and Racinais, 2015, 2016; Schmit et al, 2016; VanHaitsma et al, 2016). Trial section data demonstrated a gradual decline in MPO (and Pacing Index Change Score) as the trials progressed under hot conditions compared to the control condition ( Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat-stress (Figure 5) had a significant, negative impact on time-trial performance from a sample of 14 MPO data points per trial section MPO and for the whole trial MPO across 11 included studies (MD = −24.79 W, 95% CI = −39.52 to −10.06, p = 0.001) (Tatterson et al, 2000; Tucker et al, 2004; Abbiss et al, 2008; Altareki et al, 2009; Peiffer and Abbiss, 2011; Périard et al, 2011; Castle et al, 2012; Périard and Racinais, 2015, 2016; Schmit et al, 2016; VanHaitsma et al, 2016). Trial section data demonstrated a gradual decline in MPO (and Pacing Index Change Score) as the trials progressed under hot conditions compared to the control condition ( Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…In some of the studies, the exposure to the heat-stress prior to the time-trial (i.e., during the standardized warm-up) was ≤ 15 min in duration (Castle et al, 2012; Schmit et al, 2016; VanHaitsma et al, 2016) or longer (Abbiss et al, 2008; Altareki et al, 2009). However, in the remaining studies either no mention was made as to participants being exposed to the heat-stress prior to the time-trials, or they did not expose their participants to heat-stress in the warm-up period (Tatterson et al, 2000; Tucker et al, 2004; Peiffer and Abbiss, 2011; Périard et al, 2011; Périard and Racinais, 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes results of studies that examined the impact of heat stress on submaximal intensity aerobic performance employing either TTE or TT protocols (5,19,59,64,90,110,159,160,162,218,240,295,306,307,314). Again there is a considerable range of ambient temperatures for the control (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) • C) and heat stress (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) • C) conditions.…”
Section: History Of Research Related To Aerobic Performancementioning
confidence: 99%
“…The authors concluded that heat stress was associated with a reduced power output during self-paced exercise in highly trained men. Another cycling study examined the influence of environmental heat stress (35°C) on 4-km cycling time trial performance (Altareki, Drust, Atkinson, Cable, & Gregson, 2009). Mean performance time was reduced in 35°C compared to 13°C (95% CI of difference = 4.0 to 10.6 s; P < 0.01).…”
Section: Introductionmentioning
confidence: 99%